2023
DOI: 10.3389/fendo.2023.1159235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics and clinical-specific survival prediction in elderly patients with gallbladder cancer: a genetic and population-based study

Abstract: BackgroundBiliary system cancers are most commonly gallbladder cancers (GBC). Elderly patients (≥ 65) were reported to suffer from an unfavorable prognosis. In this study, we analyzed the RNA-seq and clinical data of elderly GBC patients to derive the genetic characteristics and the survival-related nomograms.MethodsRNA-seq data from 14 GBC cases were collected from the Gene Expression Omnibus (GEO) database, grouped by age, and subjected to gene differential and enrichment analysis. In addition, a Weighted Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Zhou et al [ 23 ] recently reported the genetic characteristics of GB carcinoma in elderly individuals over 65 years. They found increased expression of the cell cycle-related genes AURKA, AURKB, CCNA2, CCNB1, CDK1, DLGAP5, KIF11, MELK, NCAPG, and TPX2 and decreased expression of the mitochondrial function-associated genes ND1, ND2, ND3, ND4, ND4L, CYTB, COX1, COX2, ATP6, and ATP8.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [ 23 ] recently reported the genetic characteristics of GB carcinoma in elderly individuals over 65 years. They found increased expression of the cell cycle-related genes AURKA, AURKB, CCNA2, CCNB1, CDK1, DLGAP5, KIF11, MELK, NCAPG, and TPX2 and decreased expression of the mitochondrial function-associated genes ND1, ND2, ND3, ND4, ND4L, CYTB, COX1, COX2, ATP6, and ATP8.…”
Section: Diagnosismentioning
confidence: 99%
“…These genes promote cancer cell overgrowth and metastasis. In addition, Zhou et al [ 23 ] found that elderly patients were less responsive to gemcitabine and cisplatin chemotherapy, similar to immunotherapy, with high PD-L1 and CTLA-4 expression[ 23 ].…”
Section: Diagnosismentioning
confidence: 99%